2018
DOI: 10.1016/j.diabet.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence improves the Finnish Diabetes Risk Score in the detection of diabetes in a large population-based cohort: The LifeLines Cohort Study

Abstract: Skin autofluorescence is a non-invasive tool that can be used to further improve the FINDRISC for diabetes detection. The new resultant model is especially useful for reclassifying people in the intermediate-risk categories, where additional blood glucose testing is needed to confirm the presence of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Analyses in a subgroup of individuals, classified a priori as intermediate risk, showed that the SAF-based decision model had a higher sensitivity and specificity compared with fasting plasma glucose alone and the FINDRISC questionnaire, and had a performance equal to HbA 1c . Finally, our group recently demonstrated in the same Lifelines cohort that measurement of SAF is of additional value to the FINDRISC for detecting current undiagnosed diabetes [36]. Reclassification analysis showed that SAF reclassified 8–15% of the total population into more accurate risk categories.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses in a subgroup of individuals, classified a priori as intermediate risk, showed that the SAF-based decision model had a higher sensitivity and specificity compared with fasting plasma glucose alone and the FINDRISC questionnaire, and had a performance equal to HbA 1c . Finally, our group recently demonstrated in the same Lifelines cohort that measurement of SAF is of additional value to the FINDRISC for detecting current undiagnosed diabetes [36]. Reclassification analysis showed that SAF reclassified 8–15% of the total population into more accurate risk categories.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes can be prevented in high‐risk subjects by lifestyle intervention 20 thus providing strong arguments for screening risk subjects 28 . In our clinical everyday life, traditional risk factors, such as the Finnish Diabetes Risk Score (FINDRISC), 29 are commonly assessed to predict future type 2 diabetes risk and several attempts have been done to improve FINDRISC further 30 . Our data shows that both lower ISI and lower CIR were associated with a higher risk for type 2 diabetes independent of the other traditional risk factors used in FINDRISC.…”
Section: Discussionmentioning
confidence: 81%
“…AGEs can predict the severity of complications in diabetes [40]. The inclusion of skin autofluorescence in the Finnish Diabetes Risk Score improved the ability to detect undiagnosed diabetes and reclassify people in the intermediate risk category [41].…”
Section: Metabolic Healthmentioning
confidence: 99%